Topological Dissection of Proteomic Changes Linked to the Limbic Stage of Alzheimer’s Disease - Velásquez, Erika; Szeitz, Beáta; Gil, Jeovanis; Rodriguez, Jimmy; Palkovits, Miklós; Renner, Éva; Hortobágyi, Tibor; Döme, Péter; Nogueira, Fábio CS.; Marko-Varga, György; Domont, Gilberto B.; Rezeli, Melinda (Frontiers in Immunology, 2021)
Alzheimer's disease (AD) is a neurodegenerative disorder and the most common cause of dementia worldwide. In AD, neurodegeneration spreads throughout different areas of the central nervous system (CNS) in a gradual and predictable pattern, causing progressive memory decline and cognitive impairment. Deposition of neurofibrillary tangles (NFTs) in specific CNS regions correlates with the severity of AD and constitutes the basis for disease classification into different Braak stages (I-VI). Early clinical symptoms are typically associated with stages III-IV (i.e., limbic stages) when the involvement of the hippocampus begins. Histopathological changes in AD have been linked to brain proteome alterations, including aberrant posttranslational modifications (PTMs) such as the hyperphosphorylation of Tau. Most proteomic studies to date have focused on AD progression across different stages of the disease, by targeting one specific brain area at a time. However, in AD vulnerable regions, stage-specific proteomic alterations, including changes in PTM status occur in parallel and remain poorly characterized. Here, we conducted proteomic, phosphoproteomic, and acetylomic analyses of human postmortem tissue samples from AD (Braak stage III-IV, n=11) and control brains (n=12), covering all anatomical areas affected during the limbic stage of the disease (total hippocampus, CA1, entorhinal and perirhinal cortices). Overall, ~6000 proteins, ~9000 unique phosphopeptides and 221 acetylated peptides were accurately quantified across all tissues. Our results reveal significant proteome changes in AD brains compared to controls. Among others, we have observed the dysregulation of pathways related to the adaptive and innate immune responses, including several altered antimicrobial peptides (AMPs). Notably, some of these changes were restricted to specific anatomical areas, while others altered according to disease progression across the regions studied. Our data highlights the molecular heterogeneity of AD and the relevance of neuroinflammation as a major player in AD pathology. Data are available via ProteomeXchange with identifier PXD027173.